2010
DOI: 10.5194/hess-14-1109-2010
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of water and carbon fluxes using a land data assimilation system: a case study for southwestern France

Abstract: Abstract.A Land Data Assimilation System (LDAS) able to ingest surface soil moisture (SSM) and Leaf Area Index (LAI) observations is tested at local scale to increase prediction accuracy for water and carbon fluxes. The ISBA-A-gs Land Surface Model (LSM) is used together with LAI and the soil water content observations of a grassland at the SMOSREX experimental site in southwestern France for a seven-year period (2001)(2002)(2003)(2004)(2005)(2006)(2007). Three configurations corresponding to contrasted model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 53 publications
(74 reference statements)
6
56
0
Order By: Relevance
“…This option is useful for climate change impact studies , and allows the sequential assimilation of satellite LAI estimates. The latter was demonstrated at the local scale, for an unmanaged grassland site (Sabater et al, 2008;Albergel et al, 2010;Barbu et al, 2011). These studies show that representing LAI observation errors is not easy.…”
Section: Introductionmentioning
confidence: 61%
“…This option is useful for climate change impact studies , and allows the sequential assimilation of satellite LAI estimates. The latter was demonstrated at the local scale, for an unmanaged grassland site (Sabater et al, 2008;Albergel et al, 2010;Barbu et al, 2011). These studies show that representing LAI observation errors is not easy.…”
Section: Introductionmentioning
confidence: 61%
“…In order to use this information into LSMs, data assimilation techniques were implemented and tested (Demarty et al, 2007;Sabater et al, 2008;Albergel et al, 2010a;Barbu et al, 2011). Data assimilation techniques aim at improving the model simulations, which are affected by uncertainties, mainly caused by the lack of knowledge of some biophysical processes, together with errors in the atmospheric variables used as input to the models (Szczypta et al, 2011;Zhao et al, 2011).…”
Section: S Lafont Et Al: Modelling Lai Surface Water and Carbon Flmentioning
confidence: 99%
“…Four statistical indices are tabulated for each dataset: the global bias, the root mean square error (RMS), the correlation coefficient and the Nash index (Nash and Suttcliffe, 1970), which definition is given in Eq. (14) and a short interpretation can be found in Albergel et al (2010): where y iest and y iobs are respectively estimated and observed values, y i obs is the mean of observations and n is the sample size.…”
Section: In-situ Validationmentioning
confidence: 99%
“…Wang et al, 2007) to the most complex models (e.g. Rodell et al, 2004;Albergel et al, 2010) have been investigated and applied to a variety of spatial scales, from local and regional (Bastiaanssen et al, 1998;Su, 2002;Stisen et al, 2008;Miglietta et al, 2009) to global scales (Jiménez et al, 2009). Most of these studies are made for research purposes and use only selected datasets.…”
Section: Introductionmentioning
confidence: 99%